The Purpose Driven Life : What on earth am i here for. - Warren. Rick (Zondervan, 2002)
Discover and fulfill your God-given purpose by joining the more than thirty-five million others who have embarked on a spiritual journey that started with this #1 New York Times bestselling book by Pastor Rick Warren.Before you were born, God knew what your life had in store for you. His hope for you is to discover the life he created just for you--both here on earth, and forever in eternity. Let Rick Warren guide you as you learn to live out your true purpose.The Purpose Driven Life is more than a book; it's a road map for your spiritual journey. Combining thoughtful verses from Scripture with timely stories and perspectives from Warren's own life, The Purpose Driven Life will help you discover the answer to one of life's most important questions: What on earth am I here for?Throughout The Purpose Driven Life, Warren will teach you to spend time getting to know yourself and your creator in order to live your life to the fullest. Unlocking your true purpose will also reduce your stress, simplify your decisions, increase your satisfaction, and, most importantly, prepare you for eternity.Designed to be read over the course of forty-two days, The Purpose Driven Life will help you see the big picture, giving you a fresh perspective on the way that the pieces of your life fit together. Every chapter of The Purpose Driven Life provides a daily meditation and practical steps to help you uncover and live out your purpose, starting with exploring three essential questions: The Question of Existence: Why am I alive?The Question of Significance: Does my life matter?The Question of Purpose: What on earth am I here for?Each copy of The Purpose Driven Life also includes thoughtful discussion questions, audio Bible studies that go along with every chapter, and access to a supportive online community, giving you the opportunity to dive even deeper into each life-changing lesson.